Scholarship from the Cypriot Government Scholarship Foundation for my performance in the Lyceum combined with my record in the Higher Educational Institute - Markou, George (My University, 2026)
Scholarship from the Cypriot Government Scholarship Foundation for my performance in the Lyceum combined with my record in the Higher Educational Institute.
Keywords: Sciences